(untitled) (Research, Society and Development, 2021)
In this period, in which Brazil and the world were affected by the COVI-19 virus, new methodological proposals emerged and are reorganizing the way of using and learning Chemistry. Based on this reality, this study aims to understand the teaching-learning of Chemistry, as well as to identify the methodological practices that stood out in the context experienced. Therefore, a literature review was carried out using as data sources books, articles, monographs, theses, dissertations and works published in annals that currently addressed the analyzed problem. The results obtained are structured in three topics, which respectively address the characterization of the teaching-learning of Chemistry, the methodologies present in everyday practices, as well as the reorganization of the teaching of this component during the pandemic period. For the first two paragraphs, a specific time frame was not used for the information collected, this was due to the need to use the main notes that constituted the theme, regardless of the period. In the third topic, due to the particularity of the moment experienced by the pandemic, there was the need to restrict the information collected, employing works developed between the period 2020 to 2021, in order to understand how the teaching of Chemistry occurred in the previous context of the pandemic. The study developed understands that the teaching-learning of chemistry must occur in a contextualized way, with resources and methods that help in the daily construction of new conceptions about chemical science.